CHINESE TRADITIONAL PATTERNS AND TOTEM CULTURE IN MODERN CLOTHING DESIGN - Gao, X.; Yezhova, O. (Art and Design, 2023)
The purpose: explain the concept of totem in traditional Chinese patterns, and introduce representative totem elements and their implication. Analyze the traditional Chinese patterns that appear in modern clothing design. Methodology. A systematic approach was used in this research to project contemporary modern clothing design: history-analytical, literary-analytical, morphological, and comparative analysis of the creative primary source, associative means of its adaptation to the actual fashion trends. The methodology of the research is based on the systematic analysis of the design projects using elements of traditional patterns in China. Results. Studies have shown that not all widely used traditional Chinese patterns are totems, and totems are patterns with more symbolic meaning. Several representative traditional Chinese patterns are displayed. The cultural connotation of Chinese style patterns widely used in modern clothing design is revealed, and the innovative methods of patterns are also considered. The scientific novelty of this research lies in its compilation of prior studies, which help differentiate between traditional Chinese patterns and totems. Additionally, the study introduces the concepts of totem worship, reproductive worship, and soul worship that are embedded within these patterns. Practical recommendations for integrating traditional Chinese patterns into modern clothing design are also provided. Practical significance. of this study lies in its potential application to the practice of incorporating Chinese traditional patterns into contemporary clothing design. By understanding the cultural heritage and totemic elements within these patterns, designers can create innovative and culturally rich fashion pieces that pay homage to China's rich artistic history.